Bootstrapping Inequality of Opportunity in Europe. Are changes significant? - Suárez Álvarez, Ana; López Menéndez, Ana Jesús (Journal of Income Distribution®, 2019)
The aim of this article is to shed some light on the behaviour of income inequality and inequality of opportunity over time for 26 European countries. The analysis is carried out using microdata collected by the European Union Statistics on Income and Living Conditions (EU-SILC), which incorporate a wide variety of personal harmonised variables, allowing comparability between countries. The availability of this database for the years 2004 and 2010 is particularly relevant to assess changes over time in the main inequality indices and the contribution of “circumstance” to inequality of opportunity. Bootstrap methodology is used with the aim of testing if the differences between the two years are statistically significant. Results show that observed changes in inequality of opportunity and income inequality are in most cases significant and also prove the robustness of the bootstrap methods to analyse the evolution of income inequality and inequality of opportunity.